Simulation study of a wide axial field of view positron emission tomography system based on resistive plate chamber detectors - Sousa, Jorge Miguel Tavares Couceiro (2014)
Tese de doutoramento em Física, Especialidade de Física Tecnológica, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra